Educational Evaluation: Types, Processes, Challenges, and Implications for Educational Policy - Arbeni, Wawan; Naomira, Dinda; Syahrapi, Ridho Bayu; Pratiwi, Rika; Molita, Pinkan; Halim, Abdul (Holistic Science, 2025)
Educational evaluation is a crucial element in the learning process that aims to assess the effectiveness and quality of education. In this context, evaluation is not only a measurement of learning outcomes, but also includes a comprehensive analysis of various aspects that affect the educational process. Evaluation can be defined as a systematic process to determine the value of an activity or object based on certain criteria. The evaluation process includes several important stages, including evaluation planning, data collection, data analysis, and report preparation. Evaluation also serves as a tool to identify strengths and weaknesses in the learning process, as well as contributing to the development of curriculum and educational policies. Although evaluation is important, there are still many challenges faced, such as lack of resources and stakeholder resistance. Therefore, strategic solutions are needed to improve the effectiveness of educational evaluation.